2002
DOI: 10.1161/01.cir.0000033519.45615.c7
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Neuroadrenergic Effects of Moderate Dietary Sodium Restriction in Essential Hypertension

Abstract: Background-In essential hypertension, marked restrictions in dietary sodium intake cause in the short-term period an increase in muscle sympathetic nerve traffic (MSNA) and a baroreflex impairment. The present study was set out to assess on a long-term basis the neuroadrenergic and reflex effects of moderate sodium restriction. Methods and Results-In 11 untreated mild to moderate essential hypertensive patients (age 42.0Ϯ2.6 years, meanϮSEM), we measured beat-to-beat blood pressure (Finapres), heart rate (ECG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
3
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 30 publications
6
89
3
2
Order By: Relevance
“…However, in clinical situations with sustained low BP, such as heart failure, resting sympathetic activity is elevated (19). A recent study showed that MSNA remained consistently elevated over 8 wk in hypertensive subjects who switched to a low-salt diet (20). Clearly, changes in volume status and BP have a sustained effect on sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical situations with sustained low BP, such as heart failure, resting sympathetic activity is elevated (19). A recent study showed that MSNA remained consistently elevated over 8 wk in hypertensive subjects who switched to a low-salt diet (20). Clearly, changes in volume status and BP have a sustained effect on sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] They additionally include the evidence that the HT-related adrenergic overdrive retains an humoral origin, namely that it is triggered by the central and/or peripheral sympathoexcitatory effects exerted by angiotensin II, leptin, insulin 9,28,35,36 (ie, substances whose circulating plasma levels are all increased in HT). Finally, evidence has been provided that nutritional or behavioral factors, such as low sodium intake or increased alcohol consumption, may trigger marked sympathoexcitatory effects, 37,38 which may be responsible, at least in part, for the HT-related adrenergic overdrive.…”
Section: Mechanisms Responsible For the Adrenergic Overdrivementioning
confidence: 99%
“…Results regarding the effects of acute antihypertensive treatment on sympathetic baroreflex function are few and controversial. Enhanced, 7 attenuated, 8,9 or unchanged 10 baroreflex sensitivity has been reported. There have been fewer studies on baroreflex regulation of muscle sympathetic nerve activity (MSNA) during chronic antihypertensive therapy, with similarly contradictory findings.…”
mentioning
confidence: 99%